Sensorial characteristics of smoked meat of capybara - Roca, R. D.; Veiga, N.; Neto, RBD; Cervi, R. C. (Empresa Brasil Pesq Agropec, 1999)
The capybara (Hydrochoerus hydrochaeris) is a herbivore rodent, semiaquatic, and lives in a herd. It's docile with simple adaptation in confinament, and produces meat and skin of high quality. This research was designed to study the elaboration of smoked palette and smoked neck, in laboratory scale, utilizing calcium chloride marination. Chemical analysis of the capybara meat, chemical and sensorial analyses of a sensorial product were performed. The treatments were: A - smoked palette with marination; B - smoked palette without marination; C - smoked neck with marination; D - smoked neck without marination. The average chemical composition of capybara's meat was water, 76.59%; ash, 0.90%; protein, 20.04% and eter extract, 0.91%. The smoked product showed water, 67.72%; ash, 2.16%; protein, 24.93% and eter extract, 2.77%. No significant differences were found in taste, aroma, strange taste and strange aroma. The smoked palette showed better tenderness and juiciness. The sensorial properties were not affected by calcium chloride marination.